FANCD1/BRCA2 plays predominant role in the repair of DNA damage induced by ACNU or TMZ. - Natsuko Kondo; Akihisa Takahashi; Eiichiro Mori; Taichi Noda; Małgorzata Z Zdzienicka; Larry H Thompson; Thomas Helleday; Minoru Suzuki; Yuko Kinashi; Shinichiro Masunaga; Koji Ono; Masatoshi Hasegawa; et al. (PLoS ONE)
Nimustine (ACNU) and temozolomide (TMZ) are DNA alkylating agents which are commonly used in chemotherapy for glioblastomas. ACNU is a DNA cross-linking agent and TMZ is a methylating agent. The therapeutic efficacy of these agents is limited by the development of resistance. In this work, the role of the Fanconi anemia (FA) repair pathway for DNA damage induced by ACNU or TMZ was examined. Cultured mouse embryonic fibroblasts were used: FANCA(-/-), FANCC(-/-), FANCA(-/-)C(-/-), FANCD2(-/-) cells and their parental cells, and Chinese hamster ovary and lung fibroblast cells were used: FANCD1/BRCA2mt, FANCG(-/-) and their parental cells. Cell survival was examined after a 3 h ACNU or TMZ treatment by using colony formation assays. All FA repair pathways were involved in ACNU-induced DNA damage. However, FANCG and FANCD1/BRCA2 played notably important roles in the repair of TMZ-induced DNA damage. The most effective molecular target correlating with cellular sensitivity to both ACNU and TMZ was FANCD1/BRCA2. In addition, it was found that FANCD1/BRCA2 small interference RNA efficiently enhanced cellular sensitivity toward ACNU and TMZ in human glioblastoma A172 cells. These findings suggest that the down-regulation of FANCD1/BRCA2 might be an effective strategy to increase cellular chemo-sensitization towards ACNU and TMZ.